Autoantibodies from schizophrenia patients induce cerebral cox-1/iNOS mRNA expression with NO/PGE2/MMP-3 production - Ganzinelli, Sabrina Belen (2010)
We demonstrated that circulating antibodies from schizophrenia patients, which interact with cerebral M1 muscarinic acetylcholine receptors (M1 mAChRs), trigger production of nitric oxide (NO), prostaglandin E2 (PGE2) and matrix metalloproteinase-3 (MMP-3), and act as inducers of cyclooxygenase-1 (cox-1) and inducible nitric oxide synthase (iNOS) mRNA expression in the rat frontal cortex. The corresponding affinity-purified anti-M1 peptide IgG from schizophrenia patients, while stimulating cerebral M1 mAChRs, increases NOS activity, PGE2 and MMP-3 production associated with iNOS over-activity and mRNA expression. Moreover, PGE2 and MMP-3 production is the result of cox-1 expression and activity. All these effects were inhibited by pirenzepine or haloperidol and mimicked the action of the authentic mAChR agonist. Concurrent analysis of the effects of iNOS, phospholipase C, protein kinase C and calcium/calmodulin inhibition showed that antibody up-regulation of NOS activity, PGE2 and MMP-3 production is under the control of the endogenous NO signalling system. These results provide evidence of the role that cholinergic receptor antibodies play in the development of cerebral inflammation, which shows that an antibody that interacts with cerebral mAChRs can induce expression of pro-inflammatory mediators, and support the participation of an autoimmune process in a particular group of chronic schizophrenia patients.